Cellular Fibroma of the Ovary with Multiloculated Macroscopic Characteristics: Case Report - Sheila Jorge Adad; Valeria Lima Laterza; Carlos David Teixeira dos Santos; Antonio Alexandre Lisboa Ladeia; Joao Carlos Saldanha; Cleber Sergio da Silva; Luis Ronan Marquez Ferreira e Souza; Eddie Fernando Candido Murta (Case Reports in Medicine)
Ovarian fibroma is the commonest benign tumor of the ovarian stroma. The cellular subtype accounts for around 10% of ovarian fibromatous tumors. The cellular fibroma is a tumor of uncertain malignant potential that may recur or be associated with peritoneal implants. Usually these are solid tumors, sometimes with small areas of cystic degeneration. This case is reported to highlight an unusual feature for an ovarian fibroma: the tumor was predominantly cystic with a small solid part; the multiple cavities contents consisted of viscous liquid that solidified under room temperature. The multiloculated cysts, the mucinous contents, and the solid areas simulated a borderline mucinous ovarian tumor on both CT scan and gross pathologic examination.